Teaching History during Covid-19 - Maria Elisabetta Porcedda (Centro Universitario Cardenal Cisneros, 2021)
It is here reported the experience of a first classroom of an Italian Liceo during the semi-lockdown at school (students in weekly rotation), then full. Creating a participatory environment was the aim, to give all students the opportunity to acquire concrete knowledge and to develop the 21st century skills, starting from the Learning ones. So, cooperative peers in flipped classroom, were invited to: read and see teacher's selected sources (also for 3D visors); write an online document (Word), answering to questions of their peer; create a digital storytelling of the topic to orally expose online, collaborating through social media (WhatsApp) and collaborative online tools; finally, answer to a quiz (Quizziz). The obtained results concern: the engagement of the classroom, which fosters all students' essential understanding and knowledge; inclusion of weaknesses, through their active role in cooperation; inclusion of mobile-phones as democratic tool; ubiquity of learning, which reduces the distance between online and in-presence schooling; above all, fostering the achievement of the 21st century skills, particularly learning-to-learn. For all these reasons, what lockdown teaches will remain as a valid didactical lesson.